"A Fondness for Military Display": Conquest and Intrigue in South India during the First Anglo-Afghan War, 1839–40. Issue 1 (11th January 2018) - Mallampalli, Chandra
Abstract : As the East India Company prepared for its First Anglo-Afghan War (1839–42), its officials grew suspicious of a Muslim uprising within British India. They became convinced that itinerant Muslim reformers—mislabeled "Wahhabis"—were inciting princes of India's Deccan region to rebellion. This article describes how the very talk of this "Wahhabi conspiracy" not only triggered the interventionist impulses of the colonial state, but also inspired local intrigues associated with the downfall of two Indo-Afghan princes of the Deccan, Kurnool's Ghulam Rasul Khan and Udayagiri's Abbas Ali Khan. In both cases a preoccupation with the transnational Wahhabi operative masked local and sometimes petty interests, which drove the politics of these smaller regimes. The case studies of Kurnool and Udayagiri illustrate how news of events arising in one region of imperial conflict could "travel" to remote regions of India's Deccan, evolving into conspiracy narratives along the way. The discourse of conspiracy provided a pretext for military action and the annexation of territory. The story being told, however, is not simply about paranoid colonial officers who were all too eager to intervene, but is also about local entrepreneurs who knew how to exploit the situation toward their own ends.